Red Dragon Fruit Peel Extract (Hylocereus lemairei) as an Alternative Dye in Worm Egg Staining - Ary Nurmalasari; Dinda Ayunastiti; Atun Farihatun; Rahayu Nirmatul M (LPPM STIKes Muhammadiyah Ciamis, 2023)
Helminthiasis is still a problem in Indonesia, and worm infections often occur without symptoms, so the disease receives less attention. Identification can be done by several methods, one of which is by direct examination using 2% eosin dye. However, 2% eosin dye is included in synthetic dyes that can harm ul to health. The alternative used is to utilize natural ingredients. Red dragon fruit Hylocereus lemairei is a natural material that contains anthocyanin substances where in an acidic atmosphere anthocyanin substances provide a red colour so that it can be used as an alternative dye to replace eosin. The aim of this study was to determine the microscopic picture of worm egg preparations using alternative dyes of red dragon fruit peel extract. The research method used is an experimental method. The results showed that the red dragon fruit peel extract dye with a concentration variation of 2%, 5%, and 10% did not colour the worm eggs. So the red dragon fruit peel extract dye is still not optimal for use as an alternative dye for coloring worm eggs.